Soil types of Aosta Valley (NW-Italy). Issue 2 (9th December 2020) - D'Amico, M. E.; Pintaldi, E.; Sapino, E.; Colombo, N.; Quaglino, E.; Stanchi, S.; Navillod, E.; Rocco, R.; Freppaz, M.
ABSTRACT: The first soil map of the whole Aosta Valley Region was produced at the 1:100, 000 scale. We used 691 soil profiles, attributed to 16 Cartographic (soil) Units, spatialized using a Maximum Likelihood Estimation model available in ArcGIS software. Six maps were used as base layers, representing the most important soil-forming factors: parent material, vegetation/land use, mean annual precipitation, elevation, absolute aspect and slope angle. The Maximum Likelihood Estimation was followed by an expert-based check that led to a re-assignment of some wrongly attributed cartographic polygons. The validation process revealed that the User's and Producer's Accuracies were rather high (between 47.5% and 84.4% for common soil types). A particularly high pedodiversity, associated to strong geological, vegetational and climatic gradients was observed.